The Psychometric Hepatic Encephalopathy Score for Diagnosis of Minimal Hepatic Encephalopathy in Liver Cirrhosis Patient - Kumbara, Cokorde Istri Yuliandari Krisnawardani; Wibawa, I Dewa Nyoman; Widiana, I Gde Raka (The Indonesian Society for Digestive Endoscopy, 2024)
Introduction: The psychometric hepatic encephalopathy score (PHES) is a tool that can be considered as a gold standard for detecting minimal hepatic encephalopathy (MHE) in liver cirrhosis patients. The PHES must be standardized based on the local healthy population before it can be used. The purpose of this study is to standardize the PHES with Indonesian local populations and set the cutoff point of PHES so it can be used to detect MHE in liver cirrhosis patients.Methods: PHES were administered to all enrolled subjects, which are healthy subjects and cirrhosis without overt encephalopathy subjects. The PHES consists of 5 psychometric tests. The influencing factors of PHES were assessed, and equations were developed to predict the expected result of each test. Diagnosis of MHE was built upon the deviation from the normal range value of PHES.Results: In total, 236 subjects participated in this research. The influencing factors of PHES of this study were age and education years. With the cutoff point of PHES less than -4, the prevalence of MHE was 37.7%, of which 7.6%, 50%, and 50% had Child-Turcotte-Pugh (CTP) grade A, B, and C respectively.Conclusions: The standardized version of PHES can be used to diagnose MHE in Indonesian liver cirrhosis patients. The PHES in this study were affected by age and education years. MHE was diagnosed if the PHES was less than -4. The incidence of MHE was found to increase along with the increase of the liver disease severity